Treatment of Plantar Fasciitis with the Yuan-Luo Point Pair: A Clinical Case Report - Jonathan Day (Medical Association of Pharmacopuncture Institute, 2019)
This case report chronicles the treatment of a case of plantar fasciitis with acupuncture and tui na for more than six clinic visits. The patient was a 41-year-old female with plantar fasciitis for two months. A variety of acupuncture and electroacupuncture protocols were used at first, with no benefit. After the fourth and fifth visits, however, the patient experienced total relief of pain and a significant reduction in stiffness that persisted through her final visit two weeks later. These later treatments included the yuan-luo (origin-connecting) acupuncture point pair KI 3 and BL 58, which is one possible explanation for their effectiveness. The yuan-luo pair is a classical point combination with much theory behind it, yet no studies have been published regarding its practical uses in clinic. This case is an example of one practical application of the pair; further examples are needed. Keywords: acupuncture, electroacupuncture, origin connecting, plantar fasciitis, plantar heel pain, yuan-luo